Meningkatkan Motivasi Belajar Melalui Kegiatan Kolase pada Anak Kelompok B TK Pertiwi II Pringsurat Temanggung Semester II Tahun Pelajaran 2017/2018 - Hestiningrum, C. Saptiti (Pena Edukasia, 2022)
In general, classroom action research aims to increase learning motivation through collage activities for children in Group B of TK Pertiwi II Pringsurat Temanggung in the second semester of the 2017/2018 academic year. Specifically, it aims to: (1) find out the application of collage activities can increase children's learning motivation (2) To determine the magnitude of the increase in children's learning motivation after collage activities are carried out. The research was carried out in two cycles, where each cycle consists of stages planning, implementation, observation, and reflection. Cycle I consisted of two meetings, as well as Cycle II. The subjects in this study were children in Group B, with a total of 16 children. The object of this research is to increase children's learning motivation through collage activities. In this study, the data collection methods used were observation, documentation and interviews. The results showed that during the implementation of collage activities with various materials at TK Pertiwi II Pringsurat, the researchers motivated all children, especially children who were not confident. After the action was taken, in Cycle I, the child started to want to do the given task. In Cycle II the children have shown an increase in their learning motivation. From the results of the research described above, collage activities can increase children's learning motivation. The children also seemed happy in doing collage activities both in Cycle I and Cycle II. The advantages of the activities carried out are very varied, including collage activities using various basic fields and using varied and diverse materials. Through fun learning activities, children's learning motivation can develop optimally.